Optimization of AB-mix Fertilizer on Varieties of Hydroponic Lettuce (Lactuca sativa L.) - Rosnina, Rosnina; Mauliza, Sarah (Journal of Tropical Horticulture, 2020)
Lettuce (Lactuca sativa L.) is a popular leafy vegetable. Most of its varieties are eaten fresh and commonly served as a garnish in fried rice or complementary vegetables in some fast food meals such as burgers and green salads. Nowadays, most lettuce varieties are grown hydroponically, replacing the soil and feeding all nutrients through the water. A hydroponic system is also considered a solution to overcome the shortage of arable lands and good-quality water.Â  This research aims to evaluate the lettuce response towards the application of AB-mix fertilizer in the hydroponic system. This research was designed using Factorial Randomized Block Design (RBD) with two factors (AB mix concentrations and lettuce varieties) and three replications. The results revealed between AB-mix concentrations and lettuce varieties, where the application of AB-mix increased the number of leaves. AB-mix's application gave an effect to all variables observed: plant height, leaf width, leaf number, and leaf chlorophyll but insignificant to root length.